72. Digital breast tomosynthesis: Flat panel and photon counting detector comparison. (December 2018) - Loria, A.; Signorotto, P.; Campoleoni, M.; Paruccini, N.; Villa, R.; Venturini, E.; Panizza, P.; Vecchio, A. del
Abstract : Purpose: In this study three digital breast tomosynthesis (DBT) devices equipped with different flat panel detectors (FPD) and a prototype equipped with a scan-spectral photon counting detector (PCD) are compared. The aim is to evaluate if a PCD device can guarantee a comparable or even better image quality delivering lower radiation doses than FPD devices. Methods: Image quality performances were evaluated exposing two image quality DBT phantoms, Tomophan and Agatha and a homemade phantom for the evaluation of low contrast detectability (LCD). Exposures were performed in automatic exposure control (AEC) mode, both with standard (ST) and high resolution (HR) modality when available. Images with the lowest achievable post-processing were analyzed. Geometric distortion, signal-difference-to-noise ratio (SDNR), LCD with the statistical method, in-plane resolution in terms of modulation transfer function (MTF) in scan and sub-scan directions, slice-sensitivity profile (SSP) and artifact spread function (ASF) were evaluated. Results: Geometric distortion resulted comparable between PCD and FPD devices. SDNR for PCD was comparable to two of the FDP devices. PCD device showed the best LCD. In-plane resolution was higher for PCD device: FPD devices exhibit a reduction in MTF 10% between 38% and 62%, both in scan and sub-scan direction. SSP evaluation showed comparable results for PCD and one of the FPD devices, while it was up to 60% worse for the others. PCD device showed a slightly worse ASF compared to FPD devices. Delivered dose in AEC with PCD device was 50% lower than doses delivered with FPD devices. Conclusions: PCD device ensures a comparable or even better image quality than FPD devices, especially for spatial resolution and detectability of low contrast objects, delivering much lower radiation dose. Photon counting seems to be really an impressive approach to DBT.